2021
DOI: 10.47391/jpma.03-415
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of routine physical therapy with and without instrument assisted soft tissue mobilization in patients with neck pain due to upper crossed syndrome

Abstract: Objective: To determine the effectiveness of routine physical therapy with and without Instrument Assisted soft Tissue Mobilization on pain intensity, range of motion in patients with neck pain due to upper crossed syndrome. Methods: It was Randomized clinical trial. The data was collected from Physiotherapy Clinics, The Agile Institute of rehabilitation Sciences (AIRS) and National Orthopedic Hospital Bahawalpur. The study was completed from 28 August 2019 to29 February 2020 after the approval .60 patients of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…18 Similar results are seen in an international study where longer than 2 hours duration increases the risk of neck and shoulder pain along with headache, blurred vision, dryness, and eyestrain. 15 Headache with neck pain was the main complaint in 65.3% of students in our study, among which 4.2% had a headache all the time and 61.1% had slight to severe headache along with neck pain. A study conducted in India showed that 89.83% of mobile phone users reported headaches with neck and shoulder pain.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…18 Similar results are seen in an international study where longer than 2 hours duration increases the risk of neck and shoulder pain along with headache, blurred vision, dryness, and eyestrain. 15 Headache with neck pain was the main complaint in 65.3% of students in our study, among which 4.2% had a headache all the time and 61.1% had slight to severe headache along with neck pain. A study conducted in India showed that 89.83% of mobile phone users reported headaches with neck and shoulder pain.…”
Section: Discussionmentioning
confidence: 55%
“…These results are in contrast to research conducted in another medical college in Lahore stated that 48.5% preferred smartphones. 15 Whereas another research identified 95% of the medical students with neck pain who preferred to use tablets as their main device. 16 Another study with the similar findings reported that all 100% participants had flawed flexion of their back and neck while studying and/or using smartphones and tablets.…”
Section: Discussionmentioning
confidence: 99%
“…Via the updated search 14 additional trials were added (Figure 1), making a total of 35 studies including 2840 patients with neck pain. 3771…”
Section: Resultsmentioning
confidence: 99%
“…Six studies included people with a mean age below 30. 37,38,41,42,67,71 Three studies include only females, 51,57,64 three studies did not specify the proportion of females 42,58,67 and one trial included only males, 50 all other studies included on average 71.3% females.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation